Beginning programming with C++ for dummies - Davis, Stephen R., 1956- (--For dummies., 2015)
This updated guide explores the basic development concepts and techniques of C++ from a beginner's point of view, and helps make sense of the how and why of C++ programming from the ground up. Beginning with an introduction to how programming languages function, the book goes on to explore how to work with integer expressions and character expressions, keep errors out of code, use loops and functions, divide code into modules, and become a functional programmer. It covers how to master basic development concepts and techniques in C++ and get rid of bugs and write programs that work. All the code from the book and an updated C++ compiler is on the companion website. --